Development and characterization of oxaceprol-loaded poly-lactide-co-glycolide nanoparticles for the treatment of osteoarthritis - ALARÇİN, EMİNE; KERİMOĞLU, OYA; KARSLI, SEHER (WILEY, 2020)
Oxaceprol is well-defined therapeutic agent as an atypical inhibitor of inflammation in osteoarthritis. In the present study, we aimed to develop and characterize oxaceprol-loaded poly-lactide-co-glycolide (PLGA) nanoparticles for intra-articular administration in osteoarthritis. PLGA nanoparticles were prepared by double-emulsion solvent evaporation method. Meanwhile, a straightforward and generally applicable high performance liquid chromatography method was developed, and validated for the first time for the quantification of oxaceprol. To examine the drug carrying capacity of nanoparticles, varying amount of oxaceprol was entrapped into a constant amount of polymer matrix. Moreover, the efficacy of drug amount on nanoparticle characteristics such as particle size, zeta potential, morphology, drug entrapment, and in vitro drug release was investigated. Nanoparticle sizes were between 229 and 509 nm for different amount of oxaceprol with spherical smooth morphology. Encapsulation efficiency ranged between 39.73 and 63.83% by decreasing oxaceprol amount. The results of Fourier transform infrared and DSC showed absence of interaction between oxaceprol and PLGA. The in vitro drug release from these nanoparticles showed a sustained release of oxaceprol over 30 days. According to cell culture studies, oxaceprol-loaded nanoparticles had no cytotoxicity with high biocompatibility. This study was the first step of developing an intra-articular system in the treatment of osteoarthritis for the controlled release of oxaceprol. Our findings showed that these nanoparticles can be beneficial for an effective treatment of osteoarthritis avoiding side effects associated with oral administration.
Keywords: intra-articular injection; nanoparticle; osteoarthritis; oxaceprol; PLGA; INTRAARTICULAR DELIVERY SYSTEM; PLGA NANOPARTICLES; ATYPICAL INHIBITOR; SUSTAINED-RELEASE; DRUG-DELIVERY; PARTICLE-SIZE; CELL; INFLAMMATION; MICROPARTICLES; DICLOFENAC